2015
DOI: 10.1016/j.ultsonch.2014.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acoustic pressure and bubble sizes on the coalescence of two contacting bubbles in an acoustic field

Abstract: In this study, the coalescence time between two contacting sub-resonance size bubbles was measured experimentally under an acoustic pressure ranging from 10kPa to 120kPa, driven at a frequency of 22.4kHz. The coalescence time obtained under sonication was much longer compared to that calculated by the film drainage theory for a free bubble surface without surfactants. It was found that under the influence of an acoustic field, the coalescence time could be probabilistic in nature, exhibiting upper and lower li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Therefore at some point rebound will be more favourable as opposed to coalescence. However, coalescence is also influenced by the applied ultrasonic frequency that determines the time period available for it to occur [38,39]. If the pressure amplitude has sufficient intensity and the sound field nears the resonance frequency, bubbles of similar size have been observed not to coalesce or rebound, remaining in contact and side by side [34].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Therefore at some point rebound will be more favourable as opposed to coalescence. However, coalescence is also influenced by the applied ultrasonic frequency that determines the time period available for it to occur [38,39]. If the pressure amplitude has sufficient intensity and the sound field nears the resonance frequency, bubbles of similar size have been observed not to coalesce or rebound, remaining in contact and side by side [34].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…19 Moreover, it could be remarkably influenced by cathode current density, concentrations of Cu 2+ and H + ions in the electrolyte solutions and, especially, the additives for adjusting electrodeposition process. [20][21][22] For example, the addition of CH 3 COOH may notably decrease the average sizes of hydrogen bubbles because of the suppression on the coalescence of bubbles, [23][24][25][26][27] while the incorporation of HCl can effectively reduce the dimension of dendritic copper deposit particles due to acceleration of copper deposition by building chloride bridges. 28 In addition, Tan et al reported that the effect of bromide ions was similar to chloride ions, while PEG (polyethylene glycol) changed the foam structure oppositely.…”
mentioning
confidence: 99%
“…Bubble coalescence means that some smaller cavitation bubbles coalesce and form a larger bubble. Unlike the cavitation bubbles formed by rectified diffusion, bubbles formed by bubble coalescence do not undergo the cavitation cycle and do not collapse [ 28 , 29 ]. We therefore infer that cavitation bubbles in the positive and negative zones may be formed by rectified diffusion and bubble coalescence, respectively.…”
Section: Resultsmentioning
confidence: 99%